2010
DOI: 10.1099/vir.0.018986-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of atypical scrapie cases from Great Britain in transgenic ovine PrP mice

Abstract: Twenty-four atypical scrapie cases from sheep with different prion protein genotypes from Great Britain were transmitted to transgenic tg338 and/or TgshpXI mice expressing sheep PrP alleles, but failed to transmit to wild-type mice. Mean incubation periods were 200–300 days in tg338 mice and 300–500 days in TgshpXI mice. Survival times in C57BL/6 and VM/Dk mice were >700 days. Western blot analysis of mouse brain samples revealed similar multi-band, protease-resistant prion protein (PrPres) profiles, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
47
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 32 publications
14
47
1
Order By: Relevance
“…The two atypical scrapie controls, Scr2 and 51|45, gave very similar and characteristic lesion profiles (Fig. 2d, e, respectively; type A in Table 3), particularly striking in the damage caused in the white matter area W3 (basal cerebral peduncle), as expected (Griffiths et al, 2010). Of the unusual scrapie transmissions, the vacuolar profile of L4824 ( Fig.…”
Section: Selection Of Candidate Atypical Scrapie Casesmentioning
confidence: 60%
“…The two atypical scrapie controls, Scr2 and 51|45, gave very similar and characteristic lesion profiles (Fig. 2d, e, respectively; type A in Table 3), particularly striking in the damage caused in the white matter area W3 (basal cerebral peduncle), as expected (Griffiths et al, 2010). Of the unusual scrapie transmissions, the vacuolar profile of L4824 ( Fig.…”
Section: Selection Of Candidate Atypical Scrapie Casesmentioning
confidence: 60%
“…According to this definition, classical scrapie includes several strains as various distinct phenotypes can be identified in mice [33][34][35] . In contrast every time a source of atypical scrapie has been bioassayed in mice a single phenotype has been detected suggesting that atypical scrapie is attributed to a single strain 36,37) . It must be emphasized that, particularly in rodents, the phenotypes are not simply host specific but mouse line specific 30,33,38) .…”
Section: Tse Disease and Strain Characterisationmentioning
confidence: 99%
“…There were differences in the distribution and intensity of vacuolation, the distribution and the different types of PrP Sc deposits identified by IHC, and a strikingly different Western blot profile that included four bands instead of the three bands that are usually associated with animal TSEs. This new phenotype was designated Nor98 and mouse bioassays showed that it transmits only to transgenic mice and produces a phenotype that is distinct from any classical scrapie phenotype identified in these mice 36,37) . This novel disease attracted a lot of interest as it raised serious questions regarding our knowledge of TSEs and our ability to detect them reliably, as retrospective studies showed that atypical scrapie cases preexisted but they had not been diagnosed as the tests used at the time were not optimised for detecting this disease 66,67) .…”
Section: Atypical Scrapiementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Classical scrapie, no strain variability has been observed so far among isolates of Atypical scrapie (Le Dur et al, 2005;Griffiths et al, 2010).…”
Section: Agent Strains In Sheepmentioning
confidence: 99%